Assessment of polymer-based nanocomposites biodegradability - Machado, A. V. (2015)
The management of solid waste is a growing concern in many countries. Municipal solid waste is a major component of the total solid waste generated by society, and the composting of municipal solid waste has gained some attention even though a composting treatment for it is not yet widespread. It may not be realistic to replace large portions of these plastics with biodegradable materials, and it may be more important to separate plastics unsuitable for the composting process at the generating spots. However, for food packaging, there is still a great deal of interest in using biodegradable plastics that are difficult to sort at the generation spots. Under these circumstances, nanocomposites of biodegradable polymers as matrix and nanoparticles, that can be degraded along with organic wastes during composting could be a solution. Therefore, this chapter aims to give an overview on the biodegradability studies of bio-nanocomposites. It will focus on different polymers, nanocomposites containing different clay types and inorganic particles exposed under different environments.